Pengaruh Pengunaan Media Pembelajaran Berbasis Animasi terhadap Pemahaman Belajar Siswa Kelas X MAN 1 Medan: The Influence of Using Animation-Based Learning Media on Students' Learning Understanding of Class X Man 1 Medan - Mardiah, Siti; Dwi Atika Zahara; Jelita Angeli Purba; FredySyah Putra; Revita Yuni (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
The teaching and learning process in the classroom is the main means of achieving student behavioral transformation, both in intellectual, moral, and social aspects. In this process, the teacher acts as a manager of interactions between students and the learning environment through various strategies that are designed systematically. The purpose of this study is to analyze how the use of animation-based learning media impacts students' understanding of what they learn in class X IPS at MAN 1 Medan. This research applies an associative quantitative method with a survey approach through the distribution of structured direct questionnaires to understand the impact of using animation-based learning media on the learning comprehension of students in class X of the MAN 1 MEDAN program. The total population in this study includes 35 students who were selected using the total sampling technique. The validity and reliability tests were conducted to ensure the quality of the measurement tool, and the results showed that the validity met the standards and the reliability with a Cronbach’s Alpha value of 0.955. Data analysis through simple linear regression indicates that the use of animation media has a positive and significant impact on students' learning comprehension, evidenced by the t-value of 2.134 being greater than the t-table value of 1.69236 and the significance level of 0.040 being less than 0.05. This shows that animation-based learning media has a positive impact on improving students' understanding. Students find it easier to understand the lesson material when using animation-based learning media.